PENGARUH LEVERAGE TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR ( Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - Natigor Sasongko Manalu; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2019)
The aim of this study is to presents an empirical insight into the relationship between leverage and profitability of the manufacture industry in Indonesia. The companies should already listed in Indonesia Stock Exchange within 2015 until 2017. This study is a replication of the study by Saleem et al. (2015) on manufacture companies that already going public. The samples were taken by purposive sampling method and finally obtained manufacture companies that fulfill the criterias.The criterias include having complete data of financial statement, and already selling stock in the stock market. Data were analyzed using Linier Regression model, Anova, and T-test. The result shows that both financial leverage and operating leverage doesn’t affect profitabily of manufaktur company separately. But they do affect profitability together.This result shows that leverage alone doesn’t affect profitability of manufactur company, there is  a lot of other variable that may change the outcome of companies profitability.